Carcinoma of breast with medullary features: a case report in 27 year old female - Patel, Krutika; Bhagat, Vashudha M.; Gamit, Bhavna; Dave, Deepshikha (International Journal of Research in Medical Sciences, 2019)
Medullary carcinoma of breast is a rare variant of invasive ductal carcinoma of breast and its incidence is less than 5% of invasive breast carcinomas. These tumours tend to occur in younger women, with the average age reported to range from 42 to 52 years. Authors are presenting this case in a 27 years old female having single, large, well circumscribed mass in right breast for 6 months. Fine needle aspiration cytology report was proliferative lesion with atypia Histopathology report was given as carcinoma with medullary features. Immunohistochemistry showed Estrogen Receptor (ER), Progesterone Receptor (PR) and Her-2 neu negative. Authors are presenting this case of Medullary carcinoma of breast for being a specific histopathological subtype.